Mortar composition and method for producing same

A mortar composition using calcium-containing waste in fine aggregate achieves equivalent strength to conventional cement mortars, addressing reduced strength issues in waste-based aggregates and contributing to environmental sustainability by immobilizing CO2.

JP7612745B2Active Publication Date: 2025-01-14MITSUBISHI UBE CEMENT CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023070496
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-04-21
Publication Date
2025-01-14
Estimated Expiration
2043-04-21

AI Technical Summary

Technical Problem

Mortar compositions using wastes and by-products with low reactivity as aggregates often suffer reduced strength development, as seen in concrete using crushed tiles, necessitating a solution that maintains strength while reducing environmental impact and CO2 emissions.

Method used

A mortar composition comprising cement, fine aggregate, and water, where the fine aggregate contains 1.0% by mass or more of calcium-containing waste with specific properties, including 20.0% to 90.0% insoluble residue and 5.0% by mass of calcium carbonate, and a method for producing this composition by mixing calcium-containing waste with fine aggregate and cement to achieve equivalent strength to conventional cement mortars.

Benefits of technology

The mortar composition achieves strength development properties equivalent to conventional cement mortars, with excellent initial strength and contributes to reducing environmental burden and CO2 emissions by effectively utilizing waste materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612745000001
    Figure 0007612745000001
  • Figure 0007612745000002
    Figure 0007612745000002
  • Figure 0007612745000003
    Figure 0007612745000003
Patent Text Reader

Abstract

To provide a mortar composition which has strength developability at a level equivalent to that of current ordinary Portland cement and especially excellent initial strength while reducing environmental load by the effective use of wastes and by-products.SOLUTION: There is provided a mortar composition which comprises cement, fine aggregate and water. The fine aggregate contains 1.0 mass% or more and 15.0 mass% or less of a calcium-containing waste. The calcium-containing waste has an insoluble residue of 20.0 mass% or more and 90.0 mass% or less as measured in accordance with JIS R 5202:2010, contains 5.0 mass or more of calcium carbonate and has a CaO residual amount of 18.0 mass% or less after subtracting the CaO amount derived from calcium carbonate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a mortar composition and a method for producing the same. [Background technology]

[0002] CO 2 As part of our efforts to reduce CO emissions, 2 Attention is being focused on a technology that chemically produces light calcium carbonate by dissolving it in a liquid phase and reacting it with calcium. Light calcium carbonate is produced by 2 CO is immobilized in the form of stable calcium carbonate. 2 This directly contributes to reducing emissions.

[0003] Huge amounts of CO 2 When immobilizing calcium carbonate, it is possible to use waste and by-products that contain a lot of calcium and are discharged in large quantities, such as waste concrete and steelmaking slag, as a calcium source. After calcium is extracted from the waste and by-products, a large amount of extraction residue is left behind. Generally, such extraction residue is often disposed of in landfills. However, if the extraction residue can be effectively utilized, it will contribute to extending the life of final disposal sites and reducing the environmental burden.

[0004] One possible use for the extracted residue is to use the larger particle size as a partial replacement for aggregate in concrete or mortar, which will contribute to the effective use of waste and by-products.

[0005] For example, Non-Patent Document 1 proposes producing concrete by substituting crushed roofing tiles for part of the aggregate. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Manufacturing and evaluation test of concrete using crushed roof tile aggregate, Abe Kohei et al., Shimane Prefectural Industrial Technology Center Research Report, No. 47, 2011 Summary of the Invention [Problem to be solved by the invention]

[0007] When low-reactivity wastes and by-products are used as aggregates to produce mortar, there is a concern that the strength development may decrease, as in the case of concrete described in Non-Patent Document 1.

[0008] Therefore, this disclosure aims to reduce the environmental burden by effectively utilizing waste and by-products while reducing CO 2 The object of the present invention is to provide a mortar composition which contributes to the reduction of emissions, has the same strength development as mortars using current cement, and is particularly excellent in early strength. [Means for solving the problem]

[0009] One aspect of the present disclosure is a mortar composition comprising cement, fine aggregate, and water, The fine aggregate contains calcium-containing waste in an amount of 1.0 mass% or more and 15.0 mass% or less. Including mass% or less, The calcium-containing waste material is The insoluble residue measured in accordance with JIS R 5202:2010 is 20.0% by mass or more and 90.0% by mass or less, Contains 5.0% by mass or more of calcium carbonate, and The object of the present invention is to provide a mortar composition having a residual CaO content of 18.0 mass % or less, after subtracting the amount of CaO derived from calcium carbonate.

[0010] Another aspect of the present disclosure is a method for producing a mortar composition comprising cement, fine aggregate, and water, comprising: A step of obtaining fine aggregate by mixing a fine aggregate material with the calcium-containing waste so that the calcium-containing waste is contained in the fine aggregate in an amount of 1.0 mass% or more and 15.0 mass% or less; Mixing cement, the fine aggregate, and water; The calcium-containing waste material is The insoluble residue measured in accordance with JIS R 5202:2010 is 20.0% by mass or more and 90.0% by mass or less, Contains 5.0% by mass or more of calcium carbonate, and The object of the present invention is to provide a method for producing a mortar composition in which the residual amount of CaO, excluding the amount of CaO derived from calcium carbonate, is 18.0 mass % or less. Effect of the Invention

[0011] According to the present disclosure, a mortar composition and a method for producing the same are provided, which have the same strength development as mortars using current cements and are particularly excellent in early strength while reducing the environmental load by effectively utilizing waste and by-products. 2 Because it contains carbonate formed by the immobilization of CO 2 This can contribute to reducing emissions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Unless otherwise specified, the materials exemplified in this disclosure can be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the mortar composition according to the present disclosure, the content of each component in the mortar composition means the total amount of the plurality of substances present in the mortar composition, unless otherwise specified.

[0013] One embodiment of a mortar composition according to the present disclosure includes cement, fine aggregate, and water.

[0014] As the cement, any cement known in the relevant technical field can be used without particular limitation. For example, ordinary Portland cement, early-strength Portland cement, moderate-heat cement, low-heat cement, oil well cement, etc. can be used. From the viewpoints of easy availability and further improvement of the initial strength, the cement preferably contains at least one of ordinary Portland cement and early-strength Portland cement, more preferably contains at least ordinary Portland cement, and only ordinary Portland cement may be used.

[0015] The cement clinker in the cement contains C 3 S, C 2 S, C 3 A, and C 4 AF. C 3 S, C 2 S, C 3 A, and C 4 The content of each of C 2 S, C 3 S, C 2 S, C 2 S can be calculated by the Bogue formula. The Bogue formula is a formula widely used to calculate the content ratio of the main minerals in cement clinker from the content ratio of the chemical composition. By using the Bogue formula shown below, the content of tricalcium silicate (3CaO·SiO 2 O 3 S, C 3 A), dicalcium silicate (2CaO·SiO 2 O 3 S, C 2 O 3 S, C 4 AF), tricalcium aluminate (3CaO·Al

[0016] <Bogue formula> C 3S[mass%]=(4.07×CaO[mass%])-(7.60×SiO 2 [mass%])-(6.72×Al 2 O 3 [mass%])-(1.43×Fe 2 O 3 [mass%])-(2.85×SO 3 [mass%]) C 2 S[mass%]=(2.87×SiO 2 [mass%])-(0.754×C 3 S [mass%]) C 3 A[mass%]=(2.65×Al 2 O 3 [mass%])-(1.69×Fe 2 O 3 [mass%]) C 4 AF[mass%]=3.04×Fe 2 O 3 [mass%]

[0017] C in cement clinker 3 The amount of S is preferably 30.0% by mass or more, more preferably 40.0% by mass or more, even more preferably 50.0% by mass or more, even more preferably 54.0% by mass or more, and particularly preferably 56.0% by mass or more. 3 By setting the S content to the above value or more, the early strength of the mortar composition when hardened can be further improved. C in cement clinker 3 The amount of S is preferably 70.0% by mass or less, more preferably 66.0% by mass or less, even more preferably 63.0% by mass or less, even more preferably 59.0% by mass or less, and particularly preferably 57.0% by mass or less. 3 By setting the S content to the above-mentioned value or less, heat generation during hardening of the mortar composition can be suppressed.

[0018] C in cement clinker 2The amount of S is preferably 5.0% by mass or more, more preferably 10.0% by mass or more, even more preferably 12.0% by mass or more, even more preferably 15.0% by mass or more, and particularly preferably 18.0% by mass or more. 2 By setting the S content to the above value or more, the long-term strength of the hardened mortar composition can be further improved. C in cement clinker 2 The amount of S is preferably 50.0% by mass or less, more preferably 40.0% by mass or less, even more preferably 35.0% by mass or less, even more preferably 30.0% by mass or less, and particularly preferably 22.0% by mass or less. 2 By setting the S content to the above-mentioned value or less, the early strength of the mortar composition when hardened can be further improved.

[0019] C in cement clinker 3 The amount of A is preferably 7.0% by mass or more, more preferably 8.0% by mass or more, even more preferably 8.5% by mass or more, even more preferably 9.0% by mass or more, and particularly preferably 9.5% by mass or more. 3 By making the amount of A equal to or more than the above value, it is possible to produce a mortar composition that increases the amount of waste and by-products, such as coal ash, which is a raw material for cement clinker. C in cement clinker 3 The amount of A is preferably 13.0% by mass or less, more preferably 12.0% by mass or less, even more preferably 11.0% by mass or less, even more preferably 10.0% by mass or less, and particularly preferably 9.8% by mass or less. 3 By setting the amount of A to the above value or less, it is possible to further reduce the increase in the amount of heat generated when the mortar composition hardens.

[0020] C in cement clinker 4The AF amount is preferably 7.0% by mass or more, more preferably 8.0% by mass or more, even more preferably 9.0% by mass or more, even more preferably 9.5% by mass or more, and particularly preferably 10.0% by mass or more. 4 By setting the AF amount to the above value or more, it is possible to produce a mortar composition that increases the amount of waste and by-products, such as coal ash, which is a raw material for cement clinker. C in cement clinker 4 The AF amount is preferably 14.0% by mass or less, more preferably 13.0% by mass or less, even more preferably 12.0% by mass or less, even more preferably 11.0% by mass or less, and particularly preferably 10.5% by mass or less. 4 By setting the AF amount to the above-mentioned value or less, it is possible to further reduce the increase in the amount of heat generated when the mortar composition hardens.

[0021] The cement clinker content is preferably 3 mass% or more and 70 mass% or less, more preferably 9 mass% or more and 45 mass% or less, and even more preferably 18 mass% or more and 27 mass% or less, based on 100 mass% of the mortar composition.

[0022] The cement may contain gypsum. For example, gypsum dihydrate, gypsum hemihydrate, anhydrous gypsum, etc. may be used as the gypsum. One type of gypsum may be used alone, or a combination of two or more types may be used. The content of gypsum in the cement may be the same as the content of gypsum in general Portland cement. Specifically, the content of gypsum in the cement may be the same as the content of gypsum in SO 3 In terms of conversion, with the total amount of cement being 100% by mass, the content is preferably 0.5% by mass or more and 3.5% by mass or less, more preferably 0.7% by mass or more and 3.0% by mass or less, and even more preferably 1.0% by mass or more and 2.5% by mass or less.

[0023] The cement may be commercially available Portland cement or the like, or may be a mixture of cement clinker, gypsum, limestone and / or calcium carbonate, which have been separately ground and mixed together, or may be a mixture produced by simultaneously grinding two or more materials.

[0024] The cement content in the mortar composition according to the present disclosure is preferably 5% by mass or more and 75% by mass or less, more preferably 10% by mass or more and 50% by mass or less, and even more preferably 20% by mass or more and 30% by mass or less, based on the mortar composition. Setting the cement content to 5% by mass or more has the advantage of improving the strength development of the mortar composition, while setting the cement content to 75% by mass or less has the advantage of reducing the amount of heat generated during hardening of the mortar composition.

[0025] The fine aggregate according to the present disclosure includes calcium-containing waste and fine aggregate other than the calcium-containing waste (hereinafter also referred to as "fine aggregate material"). In the present disclosure, "calcium-containing waste" refers to waste that contains calcium and is derived from various waste materials that have no specific use and are normally disposed of.

[0026] The calcium-containing waste is derived from waste materials such as waste concrete, waste mortar, waste cement paste, concrete sludge, paper sludge, blast furnace slag, converter slag, electric furnace slag, slowly cooled slag, chlorine bypass dust, coal ash, biomass ash, or incineration ash. The calcium-containing waste is not the waste materials themselves, but the residues remaining after calcium is extracted from the waste materials. In other words, the calcium-containing waste in the present disclosure is the calcium-containing waste after calcium extraction. The waste material preferably contains calcium in an amount calculated as CaO of 5.0 mass % or more, more preferably 10.0 mass % or more, and even more preferably 20.0 mass % or more, from the viewpoint of enabling efficient recovery of calcium from the waste material and contributing to resource recycling.

[0027] In particular, the waste material is preferably one or more selected from waste concrete, waste mortar, and waste cement paste. In other words, the calcium-containing waste is preferably derived from waste materials selected from waste concrete, waste mortar, and waste cement paste, and more specifically, is a residue after calcium is extracted from waste materials selected from waste concrete, waste mortar, and waste cement paste. By using the residue of these waste materials as a component of fine aggregate, it is possible to effectively utilize materials that have been discarded so far and reduce environmental load. In addition, the mortar composition of the present disclosure containing calcium-containing waste has a strength development level equivalent to that of ordinary Portland cement, and is particularly excellent in early strength.

[0028] The calcium-containing waste has an insoluble residue measured in accordance with JIS R 5202:2010 "Methods for Chemical Analysis of Cement" of preferably 20.0% by mass, more preferably 30.0% by mass or more, even more preferably 40.0% by mass or more, and even more preferably 50.0% by mass or more. By setting the insoluble residue of the calcium-containing waste to the above value or more, the amount of components with large grain size and low reactivity, such as sand, can be increased, and the fluidity of the mortar composition can be improved. In addition, the calcium-containing waste has an insoluble residue of preferably 90.0% by mass or less, more preferably 75.0% by mass or less, and even more preferably 60.0% by mass or less. By setting the insoluble residue of the calcium-containing waste to the above value or less, the fine particles can be increased, and the strength development of the mortar can be improved. The insoluble residue of the calcium-containing waste can be adjusted to the above-mentioned value by, for example, crushing, grinding, sieving, classifying, or other processes to separate components that are relatively low in strength and soft, such as cement paste, from components that are highly crystalline and hard, such as sand.

[0029] The calcium-containing waste preferably contains 5.0% by mass or more of calcium carbonate, more preferably 10.0% by mass or more, more preferably 12.0% by mass or more, even more preferably 15.0% by mass or more, and even more preferably 20.0% by mass or more. By setting the calcium carbonate content in the calcium-containing waste to the above value or more, the mortar composition according to the present disclosure has a strength development at the same level as ordinary Portland cement, and is particularly excellent in early strength. In addition, CO 2 Since calcium carbonate formed by immobilization of CO is contained in a sufficient amount of calcium-containing waste, 2 This can contribute to reducing emissions. The higher the proportion of calcium carbonate contained in the calcium-containing waste, the more desirable it is from the standpoint of improving the strength development of the mortar composition according to the present disclosure; however, if the proportion of calcium carbonate is as high as about 10.0 mass %, the strength development is sufficiently improved.

[0030] The amount of calcium carbonate contained in calcium-containing waste is measured, for example, by TG-DTA. In this measurement, the weight loss in the temperature range of 500°C to 800°C is calculated as the CO2 from calcium carbonate. 2 By assuming that the decarbonation is carried out at 100%, the amount of calcium carbonate can be calculated from the weight loss.

[0031] In calcium-containing waste, the residual amount of CaO, excluding the amount of CaO derived from calcium carbonate, is preferably 18.0 mass% or less, more preferably 15.0 mass% or less, even more preferably 12.0 mass% or less, and even more preferably 10.0 mass% or less. The residual amount of CaO means the degree of calcium extraction when calcium-containing waste is obtained from waste materials such as waste concrete and waste mortar. Setting the residual amount of CaO to the above value or less means that calcium has been sufficiently extracted when calcium-containing waste is obtained from the waste materials, and therefore, from the viewpoint of effective use of calcium and the prevention of calcium from being CO 2From this viewpoint, there is no particular lower limit for the residual CaO content, but it may be 0 mass% or more, 3.0 mass% or more, 6.0 mass% or more, or 9.0 mass% or more. The amount of remaining CaO is measured by the following method. First, the total CaO content is calculated from chemical composition analysis using fluorescent X-rays. Next, the weight loss at 500°C to 800°C is determined by TG-DTA measurement and is regarded as decarbonation from calcium carbonate, and the amount of calcium carbonate is calculated by the following formula. Amount of calcium carbonate (mass%) = (weight loss from 500°C to 800°C) (mass%) x 100 / 44 The remaining amount of CaO, after subtracting the amount of CaO derived from calcium carbonate, can be calculated using the following formula. Residual amount of CaO (mass%) = Total content of CaO (mass%) - (amount of calcium carbonate) (mass%) x 56 / 100

[0032] The calcium-containing waste is R defined by the following formula (1): 2 The amount of O is preferably 2.5% by mass or less, more preferably 2.0% by mass or less, and further preferably 1.5% by mass or less. From the viewpoint of suppressing the alkali-silica reaction, it is desirable to reduce the total amount of alkali in cement and concrete. 2 It is desirable to reduce the amount of calcium-containing waste. 2 The amount of O is determined by chemical composition analysis using fluorescent X-rays. R 2 O amount [mass%]=Na 2 O+K 2 O×0.658[mass%] (1) Na 2 O and K 2 O is Na 2 O and K 2 The O content [mass%] is shown.

[0033] The calcium-containing waste has a basicity of 0.50 or more, more preferably 0.70 or more, and even more preferably 0.90 or more. In general, basicity is an index that indicates the reactivity of ground granulated blast furnace slag, and the higher the basicity, the higher the reactivity and the better the strength development. Similarly, the higher the basicity, the better the strength development when calcium-containing waste is added. From this viewpoint, there is no particular upper limit on the basicity, but it may be, for example, 3.0 or less, 2.0 or less, 1.5 or less, or 1.0 or less. The basicity of calcium-containing waste is calculated from the component values ​​of chemical component analysis by fluorescent X-rays using the following formula (2). Basicity = (CaO + Al 2 O 3 +MgO) / SiO 2 (2) In formula (2), CaO, Al 2 O 3 , MgO and SiO 2 are CaO and Al, respectively. 2 O 3 , MgO and SiO 2 The content [mass %] is expressed as

[0034] The calcium-containing waste according to the present disclosure preferably has a predetermined particle size distribution. In detail, when the calcium-containing waste is taken as 100 parts by mass, the 0.3 mm sieve residue is preferably 40 parts by mass or more, more preferably 50 parts by mass or more, and even more preferably 55 parts by mass or more. The 0.3 mm sieve residue of 40 parts by mass or more has the advantage that the proportion of large-grained components that can be used as aggregate is high and the fine particles are small, resulting in good fluidity. In addition, when the calcium-containing waste is taken as 100 parts by mass, the 0.3 mm sieve residue is preferably 90 parts by mass or less, more preferably 80 parts by mass or less, and even more preferably 70 parts by mass or less. Having a 0.3 mm sieve residue of 90 parts by mass or less has the advantage that the strength development is improved by containing a predetermined amount of fine particles.

[0035] The coarse particle ratio of the calcium-containing waste is preferably 1.50 or more, more preferably 1.70 or more, and even more preferably 1.90 or more. Having a coarse particle ratio of the above value or more has the advantage that the proportion of large-grained components that can be used as aggregate is high and the fine particles are low, resulting in good fluidity. The coarse particle ratio of the calcium-containing waste is preferably 4.00 or less, more preferably 3.00 or less, and further preferably 2.50 or less. The coarse particle ratio can be measured, for example, in accordance with JIS A 1102:2020.

[0036] Calcium-containing waste is the residue remaining after calcium is extracted from calcium-containing waste materials, and there is no particular restriction on the method of extracting calcium from the waste materials. As a method capable of efficiently and sufficiently extracting calcium from the waste materials, it is preferable to adopt a method in which the partial pressure of carbon dioxide is made higher than atmospheric pressure. Specifically, it is preferable to adopt a method comprising the following steps (a)-(c). (a) A process for preparing a powder of calcium-containing waste material. (b) A step of setting the partial pressure of carbon dioxide to more than 0.1 MPa and not more than 5.0 MPa, and dispersing or dissolving the powder in water under said partial pressure to prepare a liquid to be extracted. (c) recovering a solid residue from the liquid to be extracted.

[0037] The powdering of the waste material in the step (a) can be carried out using various conventionally known techniques. The average particle size of the powdered waste material may be set to, for example, 10 μm to 5 mm, so long as it has a large specific surface area so that calcium can be efficiently extracted from the waste material. This step includes not only the operation of actually crushing the waste material, but also the case where fine waste material containing calcium is obtained in advance, such as incineration ash discharged from a thermal power plant.

[0038] In step (b), by setting the partial pressure of carbon dioxide in the gas phase in contact with the liquid to be extracted within the above range, the calcium ion concentration extracted into the liquid phase can be increased, and the efficiency of recycling calcium from calcium-containing waste materials can be improved. From this viewpoint, it is further preferable that the partial pressure of carbon dioxide is 0.1 MPa or more and 3 MPa or less.

[0039] The components other than carbon dioxide in the gas phase can be components generally contained in the atmosphere. That is, examples of the components other than carbon dioxide in the gas phase include nitrogen and oxygen. The gas phase is conveniently a gas in which carbon dioxide is supplied to the atmosphere to increase the partial pressure of carbon dioxide.

[0040] From the viewpoint of efficient extraction of calcium, step (b) is preferably carried out by adding the finely divided waste to water under the above-mentioned carbon dioxide partial pressure and stirring for a predetermined period of time, for example, from 1 minute to 90 minutes. From the same viewpoint, the liquid to be extracted is preferably kept at 20°C or higher and 80°C or lower, more preferably at 20°C or higher and 50°C or lower, and even more preferably at 20°C or higher and 30°C or lower.

[0041] In the step (c), it is preferable to carry out the solid-liquid separation operation while maintaining the partial pressure of carbon dioxide in the gas phase within the above-mentioned range and the temperature of the liquid to be extracted within the above-mentioned range. The solid-liquid separation can be carried out using a conventionally known filtration technique. Seed crystals may also be added to the liquid phase.

[0042] The calcium-containing waste thus obtained preferably has an average particle size of 10 μm or more and 1000 μm or less from the viewpoint of improving the strength development of the mortar composition according to the present disclosure. From the viewpoint of making this advantage more prominent, the average particle size of the calcium-containing waste is more preferably 300 μm or more and 600 μm or less, and even more preferably 400 μm or more and 500 μm or less. The average particle size of the calcium-containing waste can be determined by particle size measurement by sieving, etc. As a specific method, for example, the sieving test method for aggregates in JIS A 1102:2014 can be used, and the measurement can be performed in the same manner as the sieving test for fine aggregates.

[0043] The fine aggregate according to the present disclosure preferably contains 1.0% by mass or more of calcium-containing waste, more preferably 2.5% by mass or more, and even more preferably 7.5% by mass or more. By containing 1.0% by mass or more of calcium-containing waste in the fine aggregate, materials that have been discarded up until now can be effectively utilized, and the environmental burden can be reduced. The fine aggregate preferably contains 15.0% by mass or less of calcium-containing waste, more preferably 12.0% by mass or less, and even more preferably 7.5% by mass or less. When the fine aggregate contains 15.0% by mass or less of calcium-containing waste, the mortar composition according to the present disclosure has a strength development equivalent to that of ordinary Portland cement, and is particularly excellent in early strength.

[0044] The content of calcium-containing waste in the mortar composition according to the present disclosure is preferably 0.5% by mass or more, more preferably 2.5% by mass or more, and even more preferably 5.0% by mass or more, based on the mortar composition. By setting the content of calcium-containing waste to 0.5% by mass or more, materials that have been discarded up to now can be effectively utilized, and the environmental load can be reduced. The content of the calcium-containing waste is preferably 12.0% by mass or less, more preferably 7.5% by mass or less, and even more preferably 5.0% by mass or less, based on the mortar composition. By setting the content of the calcium-containing waste to the above value or less, the mortar composition according to the present disclosure has a strength development at the same level as that of ordinary Portland cement, and is particularly excellent in early strength.

[0045] The fine aggregate material contained in the fine aggregate according to the present disclosure is not particularly limited, and various fine aggregates used in ordinary mortar compositions can be used. For example, silica sand, river sand, sea sand, mountain sand, crushed sand, hard blast furnace slag fine aggregate, blast furnace slag fine aggregate, copper slag fine aggregate, electric furnace oxidized slag fine aggregate, etc. can be used as the fine aggregate material. The fine aggregate according to the present disclosure may contain two or more of these fine aggregate materials. As defined in JIS A 0203:2014 "Terminology for Concrete", fine aggregate is an aggregate that passes entirely through a 10 mm mesh sieve and 85% or more by mass passes through a 5 mm mesh sieve.

[0046] The fine aggregate according to the present disclosure preferably has a predetermined particle size distribution. In detail, when the fine aggregate is taken as 100 parts by mass, the part passing through a 0.063 mm sieve is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.4 parts by mass or more, and even more preferably 0.5 parts by mass or more. Having the part passing through a 0.063 mm sieve of 0.1 parts by mass or more has the advantage of improving the strength development. When the fine aggregate is taken as 100 parts by mass, the part passing through a 0.063 mm sieve is preferably 3.0 parts by mass or less, more preferably 1.0 part by mass or less, even more preferably 0.8 part by mass or less, and even more preferably 0.7 part by mass or less. Having the part passing through a 0.063 mm sieve of 1.0 part by mass or less has the advantage of improving fluidity.

[0047] The water content in the mortar composition according to the present disclosure is preferably 5.0% by mass or more and 30.0% by mass or less, more preferably 7.5% by mass or more and 20.0% by mass or less, and even more preferably 10.0% by mass or more and 15.0% by mass or less. The water content within the above range has the advantage of improving fluidity and workability.

[0048] The mortar composition according to the present disclosure may contain limestone in addition to cement, fine aggregate and water. As the limestone, for example, powders mainly composed of calcium carbonate, such as limestone, limestone powder, and limestone powder, which are generally available on the market, may be used. The limestone preferably includes those conforming to the minor mixing components described in JIS R 5210:2019 "Portland cement".

[0049] The limestone content in the mortar composition according to the present disclosure is preferably 10.0 mass% or less, more preferably 5.0 mass% or less, and even more preferably 2.0 mass% or less, based on the mortar composition. By setting the limestone content to the above value or less, the strength development is good. The content of limestone in the mortar composition according to the present disclosure is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more, based on the mortar composition. 2 Contributes to reducing emissions.

[0050] The mortar composition according to the present disclosure may contain, in addition to cement, fine aggregate, and water, other components within the scope of the present disclosure, such as coarse aggregate, calcium hydroxide, silica powder, other powders containing calcium (excluding gypsum and limestone), water reducers for concrete, accelerators, and retarders.

[0051] Examples of coarse aggregates include river gravel, sea gravel, mountain gravel, crushed stone, slag crushed stone, etc. These can be used alone or in combination. Examples of these coarse aggregates include those specified in JIS A5005:2020.

[0052] The mortar composition according to the present disclosure can be suitably obtained by a production method including the following steps (d) and (e). (d) A step of mixing a fine aggregate material with the calcium-containing waste so that the calcium-containing waste is contained in the fine aggregate in an amount of preferably 1.0% by mass or more and 15.0% by mass or less. (e) Mixing cement, fine aggregate, and water. EXAMPLES

[0053] The present disclosure will be described in more detail below with reference to examples, comparative examples, and reference examples. However, the present disclosure is not limited to the following examples. Unless otherwise specified, "%" means "% by mass."

[0054] (Examples 1 and 2 and Reference Example 1) [Raw materials for mortar composition] The following materials were used as raw materials for the mortar composition.

[0055] (1) Preparation of cement clinker As the cement clinker, ordinary Portland cement clinker was used, whose mineral composition according to the Bogue formula is shown in Table 1 below. The chemical composition of the cement used in the calculation of the Bogue formula was measured in accordance with the method described in JIS R 5204:2019 "Method for X-ray fluorescence analysis of cement."

[0056] [Table 1]

[0057] (2) Preparation of plaster The gypsum used met the requirements set forth in JIS R 9151:2009 "Natural gypsum for cement."

[0058] (3) Preparation of limestone powder The limestone (LS) used was a fine powder of limestone crushed from limestone that had a calcium carbonate content of 90% by mass or more and an aluminum oxide content of 1.0% by mass or less and met the requirements for minor mixed components described in JIS R 5210:2019 "Portland cement" (Blaine specific surface area value: 7470 cm 2 / g).

[0059] (4) Preparation of calcium-containing waste Waste concrete was crushed and sieved to obtain powder with sieving openings of 2 mm or less. The powder was then poured into pure water to obtain a dispersion. The dispersion was airtightly packed in a pressure-resistant stirring tank type extraction device, and while stirring, carbon dioxide was supplied into the device and the partial pressure was increased to 1.0 MPa to extract calcium into the liquid phase. During this time, the pressure of the gas phase was monitored and the partial pressure of carbon dioxide was maintained. After that, the device was separated into a liquid phase and an extraction residue, and the liquid phase to which the seed crystals had been added was depressurized to obtain calcium carbonate. The solid matter obtained by the solid-liquid separation was collected to obtain an extraction residue. The extraction residue was dried at 105°C to remove moisture, and the desired calcium-containing waste was obtained.

[0060] The physical properties of the calcium-containing waste are shown in Tables 2 and 3. The densities shown in these tables were measured using an automatic density meter (instrument: MAT-7000, Seishin Enterprise Co., Ltd.).

[0061] The chemical components of calcium-containing waste were determined by chemical analysis using the fundamental parameter method of fluorescent X-rays (equipment used: Rigaku ZSX-100e). Ignition loss (ig.loss) and insoluble residue were measured according to JIS R 5202:2010 "Methods for chemical analysis of cement". The calcium carbonate content of calcium-containing waste was calculated assuming that the mass loss from 500°C to 800°C in TG-DTA measurement (equipment name: Hitachi High-Technologies, STA-7300, nitrogen gas flow environment, heating rate: 10°C / min) is equal to the mass of carbon dioxide generated by decarbonation of calcium carbonate.

[0062] [Table 2]

[0063] [Table 3]

[0064] (5) Preparation of fine aggregate materials Standard sand from the Cement Association was used as the fine aggregate material.

[0065] [Production of fine aggregate] The fine aggregate material and calcium-containing waste were mixed in the ratios shown in Table 4 to obtain fine aggregates A and B. The particle sizes of fine aggregates A and B are shown in Table 4. For reference, the particle sizes of calcium-containing waste and the Cement Association's standard sand are also shown in Table 4. It can be seen that the calcium-containing waste has a particle size distribution relatively close to that of the standard sand. It can also be seen that the calcium-containing waste contains about 5 mass% of fine powder of 0.063 mm or less.

[0066] [Measurement of coarse particle ratio] The coarse aggregate ratios of calcium-containing waste, standard sand, and fine aggregates A and B were measured in accordance with JIS A1102:2020. In detail, the coarse aggregate ratio was calculated by dividing the sum of the percentage of the mass of the sample remaining on each sieve of 80mm, 40mm, 20mm, 10mm, 5mm, 2.5mm, 1.2mm, 0.6mm, 0.3mm, and 0.15mm by 100. The larger the coarse aggregate ratio, the coarser the grain size. The results are shown in Table 4.

[0067] [Table 4]

[0068] [Production of mortar composition] The Portland cement clinker with the chemical composition shown in Table 1 was mixed with gypsum and SO 3 The mixture was mixed and ground to obtain a base cement. The base cement and limestone powder were mixed in the proportions shown in Table 5 to obtain a cement composition. The Blaine specific surface area of ​​this cement composition was measured in accordance with JIS R 5201:2015 "Physical Measurement Methods of Cement" and found to be 3290 cm 2 / g. The cement composition was mixed with various fine aggregates and water to obtain mortar compositions. The types of fine aggregates used and the mixing ratios of each component were as shown in Table 5.

[0069] [Evaluation of mortar compressive strength of mortar composition] The mortar compressive strength of the obtained mortar composition was evaluated using a 40×40×160 mm hardened mortar body in accordance with JIS R 5201. The compressive strengths of Examples 1 and 2 were evaluated as a compressive strength ratio when the compressive strength of the specimen of Reference Example 1 was taken as 100. The results are shown in Table 5.

[0070] [Table 5]

[0071] As is clear from Table 5, the mortar compositions produced using fine aggregates containing 5% or 10% calcium-containing waste in standard sand have mortar compressive strengths equal to or greater than those of mortar compositions produced without adding calcium-containing waste. In particular, at a material age of 7 days, the mortar compressive strength is significantly increased by adding calcium-containing waste.

Claims

1. A mortar composition comprising cement, fine aggregate, and water, The fine aggregate contains calcium-containing waste in an amount of 1.0% by mass or more and 15.0% by mass or less, The calcium-containing waste material is The insoluble residue measured in accordance with JIS R 5202:2010 is 20.0% by mass or more and 90.0% by mass or less, Contains 5.0% by mass or more of calcium carbonate, and The residual amount of CaO, which is obtained by subtracting the amount of CaO derived from calcium carbonate, is 18.0% by mass or less, When the calcium-containing waste is taken as 100 parts by mass, the 0.3 mm sieve residue is 40 parts by mass or more and 90 parts by mass or less, When the fine aggregate is taken as 100 parts by mass, the part passing through a 0.063 mm sieve is 0.1 parts by mass or more and 3.0 parts by mass or less, and the part remaining on a 2.5 mm sieve is 0 parts by mass. The calcium-containing waste has a coarse particle ratio of 1.50 or more and 4.00 or less, The calcium-containing waste has an average particle size of 300 μm or more and 600 μm or less.

2. The calcium-containing waste represented by the following formula (1) R 2 The mortar composition according to claim 1, wherein the O content is 2.5 mass% or less. R 2 O amount [mass %] = Na 2 O+K 2 O×0.658[% by mass] (1)

3. 3. The mortar composition according to claim 1 or 2, wherein the calcium-containing waste is derived from a waste material selected from waste concrete, waste mortar and waste cement paste.

4. A method for producing a mortar composition comprising cement, fine aggregate, and water, comprising the steps of: A step of obtaining fine aggregate by mixing a fine aggregate material with the calcium-containing waste so that the calcium-containing waste is contained in the fine aggregate in an amount of 1.0 mass% or more and 15.0 mass% or less; Mixing cement, the fine aggregate, and water; The calcium-containing waste material is The insoluble residue measured in accordance with JIS R 5202:2010 is 20.0% by mass or more and 90.0% by mass or less, Contains 5.0% by mass or more of calcium carbonate, and The residual amount of CaO, which is obtained by subtracting the amount of CaO derived from calcium carbonate, is 18.0% by mass or less, When the calcium-containing waste is taken as 100 parts by mass, the 0.3 mm sieve residue is 40 parts by mass or more and 90 parts by mass or less, When the fine aggregate is taken as 100 parts by mass, the part passing through a 0.063 mm sieve is 0.1 parts by mass or more and 3.0 parts by mass or less, and the part remaining on a 2.5 mm sieve is 0 parts by mass. The calcium-containing waste has a coarse particle ratio of 1.50 or more and 4.00 or less, The calcium-containing waste has an average particle size of 300 μm or more and 600 μm or less.

5. the calcium-containing waste is a residue remaining after calcium is extracted from a waste material by dissolving the calcium contained in the waste material into a liquid phase, The method according to claim 4, wherein the waste material is at least one selected from the group consisting of waste concrete, waste mortar, and waste cement paste.

6. Prepare a powder of waste material containing calcium; The partial pressure of carbon dioxide is set to more than 0.1 MPa and not more than 5.0 MPa, and the powder is dispersed or dissolved in water under the partial pressure to prepare a liquid to be extracted; The method according to claim 4 or 5, wherein the calcium-containing waste is obtained by recovering a solid residue from the liquid to be extracted.

Citation Information

Patent Citations

  • Process for the production of aggregates for making road foundations and the like

    EP2272598A1

  • Production of building material

    JP1991295839A

  • Treatment of concrete waste

    JP1999319765A

  • Method and system for producing calcium carbonate

    JP2013129543A

  • Concrete binder for blast furnace cement concrete

    JP2016023105A